Strontium isotopes in Jurassic and Early Cretaceous seawater - Jones, C; Jones, Charles Edward (1992)
﻿ The collection and analysis of a large number of belemnites and oysters with excellent biostratigraphic and diagenetic control has resulted in a highly detailed determination of the seawater Sr-isotope curve through the Jurassic and Early Cretaceous. The new data confirm the broad trends established by previous work, but the much sharper resolution of the new data allows the application of Sr-isotope stratigraphy with an optimal stratigraphic resolution of ± 1 to 4 ammonite subzones (± 0.5 to 2 Ma). The data show a general decline from the Hettangian (Early Jurassic) to a minimum in the Callovian and Oxfordian (Middle/Late Jurassic). This is followed by an increase through the Kimmeridgian (Late Jurassic) to a plateau reached in the Barremian (Early Cretaceous). In addition, there are major negative excursions in the Pliensbachian/Toarcian (Early Jurassic) and Aptian/Albian (Early Cretaceous). Stable isotope data collected from belemnites and oysters have resulted in the most extensive Jurassic δ13C and δ18O database to date. While both the carbon and oxygen data appear to give reasonable marine signals, the scatter in the data suggests that future research must document possible biological fractionation effects and develop better indicators for the diagenetic alteration of 613C and 6i 8O. The final chapter documents an unexpected correlation between sudden shifts in the Sr-isotope curve, the occurrence of positive 513C excursions, and the eruption of flood basalts. In the Jurassic and Cretaceous there is a correlation in time between sudden downward shifts in the Sr-isotope curve (Pliensbachian, Aptian, Cenomanian/Turonian), the occurance of positive 613C excursions, and the eruption of flood basalts. Each of these major downward shifts in the Sr-isotope curve is followed by a sudden upward shift, which although associated with a positive 613C excursion is not associated with an episode of flood basalt volcanism. In the Cenozoic the Sr-isotope curve no longer displays downward shifts, but the correlation continues between the occurrence of flood basalts and positive 513C excursions. Several lines of evidence suggest that the eruption of flood basalts is associated with pulses of hydrothermal activity, and that this hydrothermal activity brings about the conditions necessary for the genesis of carbon-burial events.